2019
DOI: 10.1186/s12883-019-1437-9
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth encephalopathy- a rare complication of long-standing use of bismuth subsalicylate

Abstract: Background: Drugs containing bismuth, although usually safe, may rarely cause neurotoxicity. Case presentation: We describe the case of a 44-year-old woman treated with bismuth subsalicylate for about 20 years, who developed abnormal behaviour and postural instability in two weeks. On examination, she had greyish discoloration of teeth, was confused and presented generalized myoclonic jerks. In the next days, her clinical condition deteriorated, with a reduction in alertness and more exuberant myoclonus. Brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…It has been reported that prolonged high level exposure to certain bismuth compounds can lead to altered neurofunction. Bismuth-induced neurotoxicity (or encephalopathy) is a rare side effect that has been reported in patients taking high and/or prolonged doses of bismuth subnitrate, subgallate, or subsalicylate. However, generally withdrawal of the bismuth drug leads to complete recovery in short time periods . An in vitro study from 2005 reports the reduced viability of testicular macrophages upon exposure to concentrations of bismuth citrate as low as 6.25 μM bismuth content .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that prolonged high level exposure to certain bismuth compounds can lead to altered neurofunction. Bismuth-induced neurotoxicity (or encephalopathy) is a rare side effect that has been reported in patients taking high and/or prolonged doses of bismuth subnitrate, subgallate, or subsalicylate. However, generally withdrawal of the bismuth drug leads to complete recovery in short time periods . An in vitro study from 2005 reports the reduced viability of testicular macrophages upon exposure to concentrations of bismuth citrate as low as 6.25 μM bismuth content .…”
Section: Introductionmentioning
confidence: 99%
“…Wei Bi Mei is a new bismuth-containing drug with heavy magnesium carbonate, sodium bicarbonate, and multiple Chinese herbal medicinal ingredients to treat H. pylori infection. As a heavy metal element, bismuth has the potential to damage human organs, such as the kidneys, bone joints, and central nervous system [18][19][20]. us, it is vital to evaluate the safety of Wei Bi Mei by studying the pharmacokinetics of bismuth in human body.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, bismuth mainly acts locally in the gut, and systemic absorption does not appear to be necessary for efficacy [17]. As a heavy metal element, high levels of bismuth may result in damage to the kidneys, bone joints, and central nervous system once entering into the human body [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 57% patients showed complete response, 21% had partial response, and 21% had no response. In this context, it is noteworthy that long-term use of this drug is associated with the risk of neurotoxicity ( Borbinha et al, 2019 ). Nevertheless, to determine the true benefit of bismuth subsalicylate, well-powered, prospective, placebo-controlled studies stratified by disease severity and subtypes need to be performed.…”
Section: Treatmentmentioning
confidence: 99%